On area, time, and the right trade-off - Poschmann, A. (2013)
Recently one of the most active fields of cryptography has been the design of lightweight algorithms. Often the explicit goal is to minimise the physical area for an implementation. While reducing area is an important consideration, beyond a certain threshold there is little point minimising area further. Indeed, it can be counter-productive and does not necessarily lead to the most appropriate solution. To provide a clear demonstration of this, we consider two lightweight algorithms that have been proposed for deployment on UHF RFID tags and which appear in a forthcoming ISO standard. Our results show that by choosing an implementation strategy that reduces but not necessarily minimises the area, very significant savings in time and substantial reductions to other physical demands on tag performance can be delivered. In particular, given the crucial importance of transaction time in the deployment of most contactless applications, our work illustrates that the most suitable practical implementation does not always conform to expectations.